Control of poinsetiia (Euphorbia pulcherrima var. 'Ecke's red') vegetative and reproductive growth by difference between day and night temperature. - Abdullah, Thohirah Lee; Abdul Rahman, Asiah; Abd. Rahim, Anuar; A., Khairul N. (2001)
Euphorbia pulcherrima var. Ecke's Red were grown under three difference between day and night temperature (DIP) from the start of short days until flowering. DIF had a significantly effect on vegetative growth (plant height, number of internodes, and internode length) and reproductive growth (number of days to visible bract color, number of bracts and bract diameter). Plant height were lower when the plants were grown at negative DIF. Negative DIF produced the shortest plant (24.00 em) while natural DIF gave the tal/est plant (41.00 em). The shorter plant height was a result of a lower number of internodes and shorter internode length. Positive DIF grown plants resulted in earliest visible bract color (49 days) fol/owed by negative DIF (55 days) and natural DIF (85 days). Positive DIF also gave the highest number of bracts (90.00) and diameter of bracts(30.40 em). No negative influence was observed on the quality of the plants.